Music of the first nations : tradition and innovation in native North America - Browner, Tara, 1960- (University of Illinois Press, 2009)
This unique anthology presents a wide variety of approaches to an ethnomusicology of Inuit and Native North American musical expression. Contributors include Native and non-Native scholars who provide erudite and illuminating perspectives on aboriginal culture, incorporating both traditional practices and contemporary musical influences.
Keywords: Indians of North America -- Music -- History and criticism.; Indian dance -- North America.; Danses des Peuples autochtones -- Amérique du Nord.; MUSIC -- Ethnic.; MUSIC -- Genres & Styles -- Folk & Traditional.; SOCIAL SCIENCE -- Ethnic Studies -- Native American Studies.; Ethnomusicology; Indian dance; Indians of North America -- Music; North America; United States; Folk, Ethnic & World music.; Indigenous peoples.; Criticism, interpretation, etc.; History